If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9w + 3 = 3(9 + w) Reorder the terms: 3 + 9w = 3(9 + w) 3 + 9w = (9 * 3 + w * 3) 3 + 9w = (27 + 3w) Solving 3 + 9w = 27 + 3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3w' to each side of the equation. 3 + 9w + -3w = 27 + 3w + -3w Combine like terms: 9w + -3w = 6w 3 + 6w = 27 + 3w + -3w Combine like terms: 3w + -3w = 0 3 + 6w = 27 + 0 3 + 6w = 27 Add '-3' to each side of the equation. 3 + -3 + 6w = 27 + -3 Combine like terms: 3 + -3 = 0 0 + 6w = 27 + -3 6w = 27 + -3 Combine like terms: 27 + -3 = 24 6w = 24 Divide each side by '6'. w = 4 Simplifying w = 4
| d=.5kq | | 3e^2x+12=42 | | x=2.5(x-15) | | 17x+15=25 | | 3*7x=10.48 | | 9x-18=-180 | | 5t+10=5(t+10) | | X^2+14+16=0 | | x^2+28x+12=0 | | 0=r^2-144.49 | | 2x^4+6x^2-1=0 | | 7.94=2r*3.14 | | -2x-9x=x | | 6x+10=-35-3x | | 7.94=2pir | | -3-6=-33 | | -5/7x=3 | | m+287=500 | | 2x-x+20=40 | | 48-p=3p+4 | | 24-2x=14-24 | | 96+m=249 | | -4(a+5)-6(12a-30)=0 | | 96+m=246 | | 5x-14=4x+17 | | 3(x-3)-2=3x+2 | | 8x-5=2[3x-6] | | -3/4x=-8 | | 2x+10+x+2x-20+90+90=540 | | h(x)=-6x+15 | | 2t=t-3 | | 0=r^2-309.76 |